Towards an Integrated Legal Studies Department in Indonesia: Transdisciplinary Framework for Legal Higher Education - Nasrudin, Muhamad; Sodiqin, Ali; Mujib, Abdul (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
Indonesia’s pluralistic legal system institutionalizes legal education into four departments—Legal Sciences, Islamic Legal Sciences, Hindu Legal Sciences, and Customary Legal Sciences—reflecting its colonial and post-colonial legal heritage. Yet, this segmentation fosters a fragmented curriculum that hampers graduates’ holistic legal competence and limits their capacity to uphold justice and legal certainty. Moreover, inter-departmental disparities have led to systemic exclusion from legal professions for certain groups. This paper proposes a unifying framework—grounded in systems theory, Friedman’s legal system model, and Amin Abdullah’s integration–interconnection paradigm—to merge these departments into a single Indonesian Legal Studies Department. In this model, current departments would serve as concentrations within a cohesive structure, producing graduates equipped to address contemporary legal challenges. The objective is to nurture professionals endowed with broad, integrated, and robust perspectives, enabling them to uphold legal certainty, advance substantive justice, and contribute to public welfare within a progressive legal system. It is therefore recommended that the reform of Indonesian legal education be directed toward establishing an integrated governance framework supported by a unified national curriculum, faculty capacity-building, institutional exchanges, and recognition of diverse legal traditions, in order to realize genuinely transdisciplinary legal scholarship and professional practice.